Pruritus after discontinuation of cetirizine - Amy H. Chung; Lois La Grenade; Lisa M. Harinstein (SAGE Publishing, 2019)
Background: Intense pruritus or itching emerging after discontinuation of cetirizine has been the subject of postmarketing reports submitted to the U.S. Food and Drug Administration (FDA), published in the medical literature, and discussed on the internet. To better understand and further investigate this adverse event, we analyzed cases of pruritus occurring after discontinuation of cetirizine in the FDA Adverse Event Reporting System (FAERS) database and medical literature. Methods: We conducted a retrospective study to identify and describe cases of pruritus occurring after discontinuation of cetirizine in the FAERS database and medical literature through April 24, 2017. Data collected from the reports included demographic information, reason for use, serious outcome, report source, duration of cetirizine use, time to onset of pruritus after cetirizine discontinuation, presence of associated urticaria, treatment for pruritus, concomitant comorbidities and medications associated with pruritus, rechallenge information, and patient outcome information. Results: We identified 146 cases of pruritus after discontinuation of cetirizine. Reporting frequency increased starting in 2008. The median patient age was 38 years ( n  = 141), ranging from 6 to 71 years, and cases were predominantly reported in females ( n  = 110). Most cases ( n  = 115) were submitted directly to the FDA from consumers or healthcare providers. The median duration of use of cetirizine prior to discontinuation was 24 months ( n  = 130), ranging from 0.3 to 172.2 months. The median time to onset of pruritus from discontinuation was 2 days ( n  = 91), ranging from 0.5 to 5 days. Of the 55 cases that reported discontinuation of cetirizine again after restarting, 54 reported pruritus recurrence. Conclusions: Our case series provided evidence of an association between the discontinuation of cetirizine and the development of pruritus. The mechanism by which cetirizine causes pruritus upon discontinuation is unknown. Patients and prescribers should have knowledge of this adverse event, given the widespread use and availability of cetirizine, and potential impact on patient quality of life.